Potential Cause of Decrease in Bloom Events of the Harmful Dinoflagellate Cochlodinium polykrikoides in Southern Korean Coastal Waters in 2016 - Seung Ho Baek; Yunji Kim; Minji Lee; Chi-Yong Ahn; Kyung Hwa Cho; Bum Soo Park (Toxins, 2020)
Blooms of the ichthyotoxic dinoflagellate Cochlodinium polykrikoides are responsible for massive fish mortality events in Korean coastal waters (KCW). They have been consistently present in southern KCW over the last two decades, but they were not observed in 2016, unlike in the previous years. Despite extensive studies, the cause of this absence of this dinoflagellate bloom remains largely unknown. Thus, we compared physico-chemical and biological data from along the Tongyeong coast between 2016 and the previous four years (2012–2015). The averages of water temperature and salinity in August, 2016 were significantly (p < 0.001) different from those in the previous years. The amount of Changjiang River discharge, which can affect the environmental conditions in the southern Korean coastal area via ocean currents, was larger than in the previous years, resulting in a reduction in the salinity level in August when blooms of C. polykrikoides usually occurred. Moreover, compared to previous years, in 2016, there was a weak expansion of C. polykrikoides blooms in the Goheung-Oenarodo area where C. polykrikoides blooms were annually initiated in KCW. Lastly, the strong winds from the typhoon Lionrock may also have contributed to the early termination of this dinoflagellate bloom. Together with these findings, the combination of these environmental conditions in 2016, unlike in previous years, may have inhibited the formation of C. polykrikoides blooms along the Tongyeong coast.